Implementation of ethnoscience-based electronic modules in high school biology learning: A systematic literature review - Nabila Herlinawati; S. Suhartini (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The implementation of ethnoscience-based e-modules in biology learning is an innovation that integrates science with local culture. This study aims to identify relevant biology topics, benefits, and challenges in implementing ethnoscience-based e-modules through a systematic review of the literature using the PRISMA guide. Of the 292 articles identified, eight articles were selected based on inclusion and exclusion criteria. The results showed that ethnoscience-based e-modules were effective in improving student learning outcomes, scientific literacy, critical thinking, and other 21st-century skills. The integration of local culture in the module helps students connect scientific concepts with everyday life, thus creating more relevant and meaningful learning. However, challenges such as limited technological infrastructure, teacher readiness, and student adaptation to digital learning are still major obstacles. Collaboration between educators, educational institutions, and the government is needed to overcome these obstacles, by providing adequate training and resources.